Technical Vocational Education and Training (TVET) to Empower Secondary School Learners from Low Socioeconomic Backgrounds - Mirabel, Kenechukwu T.; Sewagegn, Abatihun Alehegn; Diale, Boitumelo Moleboheng (Journal of Technical Education and Training, 2022)
Low Socioeconomic Status (SES) predisposes one to vulnerability as it entangles many challenges such as financial and low opportunities. Youths from low socioeconomic backgrounds often encounter steep adversities that may potentially halt their educational pursuits. Without the right and necessary empowerment coined as skill development within the high school system, these youths may remain vulnerable to poverty, socially reliant and dependent on government support and grants. Therefore, the researchers propose a paradigm shift in the South African educational system to ensure that these learners do not lag in their learning. An effective program that will target their academic and practical skills needs is necessary to motivate them to learn and empower them to achieve financial independence, self-reliance, and productivity. Skills development in TVET will be the glue between their education and the world of work for these learners. Thus, the purpose of the study was to advocate for TVET provision as an empowering tool to elevate the Socioeconomic Status of the learners from a low socioeconomic background at a Johannesburg school. The target population was youths from a low socioeconomic background. The sample size was determined by availability of participants and manpower, thus the seven participants used whom were all from a school that caters for vulnerable learners. A purposive sampling was enforced for accurate representation of the population. Data collected through qualitative methods were properly analysed through thematic analysis. The findings of this study indicate a need for implementation and acquisition of skills through Technical Vocational Education and Training (TVET) to break the chain of poverty and propel these youths to a better future and more fulfilled lives.